2023
DOI: 10.1111/apm.13323
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of the AIM2 gene in response to Helicobacter pylori along with the decrease of NLRC4 inflammasome is associated with peptic ulcer development

Abstract: Helicobacter Pylori (H. Pylori) cause peptic ulcer disease (PUD), but the inflammasome's role in PUD is not well understood. Therefore this study has investigated inflammasome compartment expression and IL‐1β production in gastritis (G) and peptic ulcer disease. This study was based on gene expression of inflammasome compartments on stomach biopsies of 50 patients with PUD as cases and 50 individuals with gastritis as controls. The expression of NLRC4, ASC, IL‐18, and serum IL‐1β decreased in the PUD group com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Moreover, the HP+ gastritis tissues showed a higher AIM2 gene expression than HP-gastritis tissues, and the same trend was observed in HP+ peptic ulcer disease tissues. 60 H. pylori infection upregulates mRNA and protein level of AIM2 in human and mouse gastric tissue. In H. felis-infected Aim2−/− mice, stomach inflammation was less severe, along with less immune cells infiltration, attenuated proliferation and apoptosis in gastric epithelial cells and immune cells, lower protein levels of caspase-1 and IL-1β, compared with H. felis-infected wild-type mice, which uncovers a pathogenic role for AIM2 inflammasome in H. pylori-induced gastric disease.…”
Section: Aim2 Inflammasomementioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the HP+ gastritis tissues showed a higher AIM2 gene expression than HP-gastritis tissues, and the same trend was observed in HP+ peptic ulcer disease tissues. 60 H. pylori infection upregulates mRNA and protein level of AIM2 in human and mouse gastric tissue. In H. felis-infected Aim2−/− mice, stomach inflammation was less severe, along with less immune cells infiltration, attenuated proliferation and apoptosis in gastric epithelial cells and immune cells, lower protein levels of caspase-1 and IL-1β, compared with H. felis-infected wild-type mice, which uncovers a pathogenic role for AIM2 inflammasome in H. pylori-induced gastric disease.…”
Section: Aim2 Inflammasomementioning
confidence: 94%
“…59 And H. pylori-seropositive (HP+) peptic ulcer disease patients had a higher serum IL-18 level together with enhanced NLRP1 and NLRP3 expression compared with H. pylori-seronegative (HP-) individuals, promoting H. pylori to develop peptic ulcers. 60 Meanwhile, statistical analyses from 51 genetic polymorphisms in 310 ethnic Chinese also revealed a strong association between the joint effect of H. pylori infection and the selected polymorphisms in the NLR pathway (CARD8, NLRP3, NLRP12, NLRX1, and caspase-1) and gastric cancer. 61 At present, the known factors that can induce and activate NLRP3 inflammasome in H. pylori infection mainly come from the virulence factors of H. pylori, including CagPAI, VacA, CagA, and Urease B subunit (UreB).…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…The NLRs and NLR signaling pathways may also play an important role in the progression of H. pylori-associated gastritis. A study in 2023 on peptic ulcer disease found that the expression of NLRC4, NLRP12, IL-18 and IL-1β decreased significantly in patients of peptic ulcer disease compared with those of only H. pylori-associated gastritis [74].…”
Section: Gastritismentioning
confidence: 99%
“…The progression of gastritis to gastric cancer is closely linked to the differential expression of various inflammatory cytokines 20 22 . Key cytokines identified as playing a crucial role in the development and progression of gastritis include IL-1β, IL-6, IL-8, IL-12, IL-18, and TNF-α 23 26 . The roles of these cytokines range from modulating the immune response to directly influencing the inflammatory pathways within the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%